New Playwriting Strategies : Language and Media in the 21st Century. - Castagno, Paul C. (Taylor & Francis, 2011)
New Playwriting Strategies has become a canonical text in the study and teaching of playwriting, offering a fresh and dynamic insight into the subject. This thoroughly revised and expanded second edition explores and highlights the wide spread of new techniques that form contemporary theatre writing, as well as their influence on other dramatic forms. Paul Castagno builds on the innovative plays of Len Jenkin, Mac Wellman, and the theories of Mikhail Bakhtin to investigate groundbreaking new techniques from a broad range of contemporary dramatists, including Sarah Ruhl, Suzan Lori-Parks and Yo.